2001
DOI: 10.1590/s0102-35862001000600001
|View full text |Cite
|
Sign up to set email alerts
|

Timoma: discussão sobre tratamento e prognóstico

Abstract: ObjetivoLocalizado em sua porção anterior, é o tumor mais freqüente desse compartimento, compreendendo aproximadamente de 20 a 30% das massas mediastinais em adultos (1) . Os pacientes com timoma podem apresentar quadro clínico não muito específico: tosse, dispnéia, dor torácica, perda de peso, queda do estado geral. Porém, alguns pacientes são diagnosticados por radiografias de tórax em exames de rotina -que mostram opacidade homogênea no mediastino ântero-superior -ou por apresentar miastenia gravis associad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
9
0
5
Order By: Relevance
“…(10)(11)(12) In a study involving 104 patients, of which 85.6% were submitted to complete resection and 25% received adjuvant treatment, 2 patients were treated with chemotherapy, 19 with radiotherapy and 5 received a combination of the two treatments. (13) In another study, the authors evaluated a sample of 100 patients and found the ten-year survival rates to be 92%, 87%, 60% and 35%, respectively, for those with stage I, II, III and IV tumors. (14) The mean interval of recurrence for patients with stage I tumors is ten years, compared with five years for patients with stage II, III or IV tumors.…”
Section: Discussionmentioning
confidence: 99%
“…(10)(11)(12) In a study involving 104 patients, of which 85.6% were submitted to complete resection and 25% received adjuvant treatment, 2 patients were treated with chemotherapy, 19 with radiotherapy and 5 received a combination of the two treatments. (13) In another study, the authors evaluated a sample of 100 patients and found the ten-year survival rates to be 92%, 87%, 60% and 35%, respectively, for those with stage I, II, III and IV tumors. (14) The mean interval of recurrence for patients with stage I tumors is ten years, compared with five years for patients with stage II, III or IV tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The SVC syndrome is usually associated with malignancy and poor prognosis [5]. These cases include lung cancer in advanced stages (57%), mediastinal tumors (20%), and solid metastases (5%) [4].…”
Section: Discussionmentioning
confidence: 99%
“…There are discrepancies in the literature regarding the best methods for staging and classifying the disease. The most important methods are of Masaoka et al, which determines the degree of involvement of the disease, clinically and pathologically, and the French Study Group on Thymic Tumors (GETT system), which is based on surgical and pathological aspects of the tumor [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, patients with benign tumors present 10-year survival rates of 82.6% and with malignant tumors the mean 5-year survival rate is 33.5% [8].…”
Section: Fig 2 -Pre-operative Computer Tomography (A) and Chest Radimentioning
confidence: 99%